A secure dynamic adaptive routing technique using game theory in wireless sensor network - A, Muruganandam.; R, Anitha. (International Journal of Engineering and Technology, 2018)
A Wireless Sensor Network (WSNs) is popular developing the field in industrial and other major markets. Wireless data security is the central theme in the WSNs application where security of transmitted data is more concerned. Due to the significant concentration of energy efficiency and performance analysis in WSN, providing secured communication is a challenging issue. To overcome this interdependent problem Game theory can be used. Game theory is applied here to select different routes to transfer the data from source to destination. The performance of the WSNs can be increased by providing security for transmitted data. The graph for throughput, end to end delay, delivery, and packet loss ratio are generated using NS2 simulation tool.